PS-024 Monitoring of adverse drug reactions in patients treated with new oral anticoagulants. (24th February 2014) - Freire, I; Fonseca, MO; Pereira, F; Guardado, M; Martinez, J
Abstract : Background: Data on the adverse effects of newly marketed drugs are limited. The monitoring of adverse drug reactions (ADR) through active pharmacovigilance is vital to patient safety. The new oral anticoagulants dabigatran etexilate and rivaroxaban were added to the hospital form of our hospital in 2012 and were included in a system of active pharmacovigilance implemented by the pharmaceutical services, to assess the safety profile. Purpose: To identify and classify adverse drug reactions (ADRs) of the new oral anticoagulants dabigatran etexilate and rivaroxaban through a system of active pharmacovigilance. Materials and methods: From September 2012 to April 2013, a prospective study was conducted at the university teaching hospital Cova da Beira Hospitalar Centre, Covilhã, Portugal. The study included inpatients and outpatients followed by the clotting service of our Hospital, treated with dabigatran etexilate or rivaroxaban. Questionnaires were sent to doctors and nurses regarding inpatients treated with drugs or who discontinued the treatment and/or required symptomatic treatment of ADRs. Questionnaires were also given to outpatients, completed with information from the doctor. The information obtained regarding patient demographic data, diagnosis, suspected ADR and concomitant drugs was recorded in the active pharmacovigilance printed form by a hospital pharmacist. ADR severity and causal relation was classified according to Portuguese Pharmacovigilance System criteria. Results: The study included 67 patients, 41 of whom were treated with dabigatran (average age of 71, 25 male) and 26 patients with rivaroxaban (average age of 62.5, 13 male). Dabigatran was used for prevention of stroke and systemic embolism in adult patients with non-valvular atrial fibrillation with one or more risk factors. In this group, 27 patients reported adverse events (65.8%). 61 ADR were reported by patients, the most common being gastrointestinal adverse effects (64%), 10 episodes of bleeding (16.3%) mostly not serious. Two ADR were considered serious (3.3%) corresponding to two cases of gastrointestinal bleeding, requiring discontinuation of dabigatran treatment and administration of activated prothrombin complex concentrates; both patients recovered. A causal relationship was likely (86.8%). Rivaroxaban was used for primary prevention of venous thromboembolism in patients undergoing elective total elective arthroplasty of hip or knee. In this group, 12 patients reported adverse events (46%). 59 ADR were reported by patients, the most common being gastrointestinal adverse effects (44%), 4 episodes of bleeding (6.7%) none considered serious after medical evaluation. One was considered a severe ADR (1.7%) corresponding to a case of rash which required discontinuation of treatment. A causal relationship was likely (81.4%). All ADR detected were documented in the drugs summary. Conclusions: The ADR detected were mostly not serious, gastrointestinal symptoms being the most common. We identified 6.7% of non-serious bleeding associated with rivaroxaban and 16.5% of bleeding associated with dabigatran, of which 3.3% were considered severe gastrointestinal haemorrhages. No conflict of interest.